A empregabilidade das pessoas com deficiência: uma análise da inclusão social no mercado de trabalho do município de Bauru, SP - Violante, Rômulo Rodrigues; Leite, Lúcia Pereira [UNESP] (My University, 2011)
Based on the precepts of social inclusion, this research objected to examine the employment of people with disability(PWD), according to decree nº 3.298 which establishes hiring quotas for PWD in companies with 100 or moreemployees. Interviews were made with employees of HR departments in 12 different companies located in the westside of the state of São Paulo, based on a structured script. All the interviews were transcripted and gathered inanalysis categories. The results showed that one third of private companies comply with the regulation foremployment of PWD. Corporate policies prioritize hiring of people whose disabilities do not demand structuralmodifications in the work environment, or those whose disabilities represent a positive aspect for production lines.The majority of the interviewed understand disabilities as an individual phenomenon. Although they have talkedabout equal rights for everyone, the majority of them do not present a consistent speech based on the precepts ofsocial inclusion, for they fail to promote actions for supporting the population with disabilities and expecting thatthose with disabilities are the ones responsible to adjust themselves to all imposed conditions.

Amparada nos preceitos da inclusão social, esta pesquisa objetivou examinar a empregabilidade das pessoas comdeficiência (PCD) em atendimento ao Decreto 3.298, que estabelece cotas para contratação de PCD para empresascom 100 ou mais funcionários. Foram entrevistados funcionários do setor de recursos humanos de 12 empresas demédio e grande porte de um município do oeste paulista, à luz de um roteiro estruturado. As entrevistas foramintegralmente transcritas, categorizadas pelo critério da análise de conteúdo. Os resultados apontam que um terçodas empresas privadas cumpre a regulamentação. As políticas empresariais priorizam contratações de pessoas cujasdeficiências não exijam modificações estruturais no ambiente de trabalho, ou que então represente aspecto favorávelà produção. A maioria dos entrevistados concebe a deficiência como um fenômeno de caráter individual. Emboratenham discursado sobre direitos iguais a todas as pessoas, grande parte ainda não apresenta discurso condizentecom os pressupostos inclusivos, pois deixa de realizar ações de suporte para atender essa demanda populacional,esperando que o próprio indivíduo se ajuste às condições postas.
Keywords: Person with disability; Job market; Social inclusion; Pessoa com deficiência; Mercado de trabalho; Inclusão social